PKM KEWIRAUSAHAAN PENGOLAHAN DAUN KELOR MENJADI REMPEYEK - Hasbi Hasbi; Mitha Evalista; Ika Wisudawaty; Muh. Rizah Putrawan; Irfan Yunus (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Moringa leaves are a plant that has many health benefits, rich in vitamins, minerals and antioxidants. Vitamins A, C, and E contained in Moringa leaves are very important for maintaining healthy eyes, skin, and improving the immune system. The current problem is the abundance of Moringa leaves and limitations in how to process them, so the author took the initiative to create a new variation by combining Moringa leaves into peanut brittle. This innovation not only provides added value to peanut brittle, but also utilizes the advantages of Moringa leaves in a more creative and varied way. The methods used in this activity include lectures, questions and answers or discussions, and training. The results obtained were (1) The participants responded well to the training on making peanut brittle from Moringa leaves; (2) The high interest and motivation of the training participants really supports the transfer of knowledge and skills from the service to the training participants, so that the training material provided can be absorbed by all; and (3) The training product for making peanut brittle from Moringa leaves can be consumed daily and can be used as an entrepreneurial product.